2022
DOI: 10.1149/1945-7111/ac653b
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Design of High Energy All-Solid-State Li Batteries with Hybrid Electrolytes

Abstract: As the aircraft industry becomes more committed to sustainable aviation, hybrid-electric propulsion systems containing batteries with higher specific energy have attracted attention as a means to reduce fuel consumption. Future aircraft could benefit from next-generation chemistries like oxide-based solid-state Li battery (SSB) technologies. However, producing and evaluating a wide range of design parameters for maximizing the specific energy of SSB experimentally is both time- and resource-intensive. Physics-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…We use a hybrid electrolyte with 12.7 vol% LLZTO, as this configuration yielded the best performance among hybrid electrolytes at a relatively high C-rate, i.e., 1C. 22 The electrolyte properties of this hybrid electrolyte are based on reported experimental data in Ref. 24, which accounts for any impurity or degradation effects present in real material.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We use a hybrid electrolyte with 12.7 vol% LLZTO, as this configuration yielded the best performance among hybrid electrolytes at a relatively high C-rate, i.e., 1C. 22 The electrolyte properties of this hybrid electrolyte are based on reported experimental data in Ref. 24, which accounts for any impurity or degradation effects present in real material.…”
Section: Methodsmentioning
confidence: 99%
“…Following Wolff's work, our group developed an ASSB model for hybrid electrolytes, including polymer and oxide electrolytes, to estimate the optimal electrode design using a global optimisation algorithm to attain higher specific energy. 22 We found that a hybrid electrolyte based on 12.7 vol% of garnet, i.e. LLZTO, based on the current manufacturing limitations of ASSB, is the best choice.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The numerical approach to the ASS-LA modelling consists of adapting the P2D electrochemical model to the solid (or hybrid) electrolyte. The main changes affect the mass conservation and the charge balance in the electrolyte [22]. The model is extended with a microstructure surrogate model to derive the effective macroscopic parameters.…”
Section: Battery Technology Exploration In Imothepmentioning
confidence: 99%
“…Two sets of calculations are performed. The first set, reported in [22], aims at identifying hybrid polymer-ceramic solid electrolytes with high GED and optimising the best (V1 in Figure 5) for three cell designs: energy, power or balanced for 1C discharge. For V1, a maximum GED of 450 Wh/kg at cell level can be reached, but with very limited power output.…”
Section: Battery Technology Exploration In Imothepmentioning
confidence: 99%